Association of Modic Changes with Low Chronic Low Back Pain - Shah, Akbar; Ishfaq, Asim; Malik, Muhammad Jalil; Akmal, Muhammad; Javed, Amna; Haider, Adnan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the association of Modic changes with chronic low back pain in the adult population Study Design: Comparative cross-sectional study.Place and Duration of Study: Department of Neurosurgery, Combined Military Hospital, Lahore Pakistan, from Jan to Mar 2022.Methodology: All the patients who were diagnosed with chronic low back pain by Neurosurgeon were included in the study.Detailed history and physical examination were conducted on all the patients diagnosed with chronic low back pain. MRI spine was performed on all the study participants for Modic changes. Relevant socio-demographic factors were associated with different types of Modic changes in patients included in our analysis.Results: Out of 300 patients managed for chronic low back pain during the study period, 201(67%) were male, while 99(33%) were female. 172(57.3%) had no Modic changes, 33(11%) had Type-I changes, 80(26.7%) had Type-II changes, and 15(5%) had Type-III Modic changes. Advancing age, female gender and presence of comorbid illness had a statistically significant relationship with Modic changes in study participants (p-value